Analgesic Activities of Synthesized Divalent Metal Complexes of Tolfenamic Acid - Mazumder, Md Mahabob Ullah; Sukul, Abhijit; Saha, Sajal Kumar (Dhaka University Journal of Pharmaceutical Sciences, 2016)
The objective of the study was to synthesize and to uncover the potentially interesting biological peripheral and central analgesic activities of some new divalent metal complexes of tolfenamic acid. The inception of the study was carried out with the formation of complexes [Cu(tolf)2(H2O)]2, [Co(tolf)2(H2O)2] and [Zn(tolf)2(H2O)] through the reaction of tolfenamic acid, a potent anti-inflammatory drug, with Cu, Co and Zn salts. Characterization of the metal complexes of tolfenamic acid was furnished with spectral (FTIR, UV-Visible) and calorimetric (DSC) analysis. The peripheral analgesic activities of the complexes were investigated by acetic acid-induced writhing method. In peripheral analgesia model, Cu, Co and Zn complexes of tolfenamic acid showed significantly promising analgesic potency at a dose of 25 mg/kg body weight with percentage of inhibition of acetic acid induced writhing by 49.67% (p < 0.01), 67.32% (p < 0.001) and 72.55% (p < 0.001), respectively compared to the standard tolfenamic acid 46.41%. Radiant heat tail-flick test was used to observe the central analgesic activity which showed analgesic effect evidenced by % elongation time (34.59%, 25.34% and 53.08%), respectively compared to that of morphine 2 mg/kg body weight at an equimolar dose of tolfenamic acid at 10 mg/kg body weight after 30 minutes. In the final analysis, it can be stipulated that newly synthesized stable metal complexes of tolfenamic acid have promising pharmacological effects like peripheral and central analgesic potency. Therefore, these complexes may be the better therapeutic options in the near future however it needs further extensive analysis in the pharmacokinetics, pharmacodynamics and toxicology perspective. Dhaka Univ. J. Pharm. Sci. 15(1): 89-96, 2016 (June)